2009
DOI: 10.1038/nchembio.276
|View full text |Cite
|
Sign up to set email alerts
|

Relating diffusion along the substrate tunnel and oxygen sensitivity in hydrogenase

Abstract: In hydrogenases and many other redox enzymes, the buried active site is connected to the solvent by a molecular channel whose structure may determine the enzyme's selectivity with respect to substrate and inhibitors. The role of these channels has been addressed using crystallography and molecular dynamics, but kinetic data are scarce. Using protein film voltammetry, we determined and then compared the rates of inhibition by CO and O2 in ten NiFe hydrogenase mutants and two FeFe hydrogenases. We found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
336
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(354 citation statements)
references
References 36 publications
18
336
0
Order By: Relevance
“…The nuanced role of the protein matrix in influencing catalysis is not restricted to oxygen delivery. In hydrogenases, gas channels have been reported to selectively filter molecules such as oxygen and carbon monoxide to prevent inactivation at the active site (12,17,35). Recent investigation of heme nitric oxide/oxygen binding domains has suggested that tunnels not only direct gases to the heme iron but also modulate reversible gas binding (16).…”
Section: Discussionmentioning
confidence: 99%
“…The nuanced role of the protein matrix in influencing catalysis is not restricted to oxygen delivery. In hydrogenases, gas channels have been reported to selectively filter molecules such as oxygen and carbon monoxide to prevent inactivation at the active site (12,17,35). Recent investigation of heme nitric oxide/oxygen binding domains has suggested that tunnels not only direct gases to the heme iron but also modulate reversible gas binding (16).…”
Section: Discussionmentioning
confidence: 99%
“…1B). Many kinetic, spectroscopic, and structural techniques are available to characterize these enzymes, but except for gas transport (19,24,25), there is no tool allowing the direct measurement of the rates of the individual steps. Each technique provides useful but only fragmented and indirect information, and ingenious approaches have to be used to learn about the rates of individual steps in the catalytic cycle based on a global measurement of turnover rate (29,42).…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme Production-The Strep-tagged WT and variant were constructed using bacterial strains, plasmids, growth conditions, site-directed mutagenesis strategy, and the enzyme purification protocol as described in references (24,25). The aerobically purified WT enzyme exhibits a UV/visible spectrum of a non-heme protein with a broad absorption peak around 400 nm indicative of the three FeS clusters harbored by the small subunit.…”
Section: Methodsmentioning
confidence: 99%
“…This was based on the observation that two highly conserved residues (valine 74 and leucine 122) at the end of the channel in O 2 -sensitive Hases are replaced by more bulky residues (isoleucine and phenylalanine) in regulatory Hases that control Hase gene expression and are resistant to O 2 . [123] Depending on the mutation, mutants of valine 74 were shown to either decrease the rate of O 2 diffusion to the active site, [124,125] or even to tend to acquire the phenotypes of O 2 -sensitive Hases, most probably because of faster electron-transfer rate between the active site and the closest FeS cluster (proximal cluster). [126,127] Reduction of the channel size is however not sufficient to provide O 2 tolerance.…”
Section: Chemelectrochem Reviews Wwwchemelectrochemorgmentioning
confidence: 99%